One-pot Synthesis of Aurones through Oxidation-cyclization Tandem Reaction Catalyzed by Copper Nanoparticles Catalyst - Yu, Min; Liu, Guangxiang; Han, Chengyan; Zhu, Li; Yao, Xiaoquan (Letters in Organic Chemistry, 2018)
Aurones were synthesized through an oxidation-cyclization tandem reaction of 2-(1- hydroxyprop-2-ynyl)phenols catalyzed by copper nanoparticles (Cu NPs) with bipyridine as the ligand. In the reaction, oxygen worked as a green and mild oxidant to give the best results. Cu NPs were dually activated by bipyridine ligand and water, and showed highly efficient catalytic activities to the oxygen oxidation and the cylization to give aurones and flavonoids.
Keywords: Aurones